Implementation of Socio-Utopian Ideas in Literature of 1970s: The functions and Role of Idyllic Chronotope in the novels of S. Zalygin The Commission and R. Anaya The Heart of Aztlan - Tatiana V. Voronchenko; Ekaterina V. Fyodorova (RUDN Journal of Studies in Literature and Journalism)
The comparison of the novels The Commission (1976) by Russian Soviet writer Sergey Zalygin and The Heart of Aztlan (1976) the American author of Mexican origin (Chicano) Rudolfo Anaya, published at the same time on different continents, is determined by the attempts of famous 20th century novelists to identify possible ways to achieve social harmony in the changing historical reality. The article examines the multi-functionality of the idyllic chronotope in the application of socio-utopian ideas by the writers of the 1970s. The novelty of the study is specified by strengthening the emphasis on the unconditional role of the idyllic chronotope in revealing the ideological and thematic content, assessing the dimension of the author’s personality and the importance of his contribution to world literature. The world view, genre-forming and plot-forming functions of the idyllic chronotope are singled out, its world-modeling role in the literary works is determined. It is established that in the novel of S. Zalygin the idea of harmonizing the social order acquires the form of “memories of the future”, because the image of Belyi Bor, going back to Belovodye, symbolizes the “lost paradise” of the patriarchal idyll of the Russian village. R. Anaya recreates the image of Aztlan, the spiritual ancestral home of the Aztecs, which becomes a reference point in determining the national identity of Mexican Americans in the process of their self-definition and denotes the hope for a successful construction of a better future.